KAJIAN KINEMATIKA GERAKAN SERVIS ATAS SEPAK TAKRAW - Willy Hope Sigalingging; Syairul Maktum Ritonga; Husnul Khotimah hsb; Ibrahim Wiyaka; Dicky Edrwan Daulay (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the kinematics of the overhead serve movement in sepak takraw. The focus of the study includes joint angles, movement speed, and body coordination during the serve. The method used is descriptive quantitative with observation techniques using video recordings analyzed frame by frame. The research subjects consisted of university-level sepak takraw athletes. The results show that the success of the overhead serve is influenced by the coordination between the initial movement, leg swing, and contact with the ball. Optimal angles at the hip, knee, and ankle joints contribute significantly to the speed and accuracy of the serve. Thus, understanding the kinematics aspects can improve the effectiveness of training and athlete performance.